2020
DOI: 10.1093/jjco/hyaa104
|View full text |Cite
|
Sign up to set email alerts
|

Impact of reduced smoking rates on lung cancer screening programs in Japan

Abstract: Background In Japan, lung cancer screening by annual chest radiography has been performed for the past 30 years. However, changes in risk factor status may have influenced the efficiency of current organized lung cancer screening program. The purpose of this study was to clarify whether the reduced smoking rate in younger Japanese affects the efficiency and effectiveness of lung cancer screening. Methods We investigated chron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
1
0
0
Order By: Relevance
“…They also reported that smoking increased the lifetime risk of VFs by 13% and 32% in women and men, respectively. This study demonstrated a significant decrease in the smoking rate of older adults in accordance with the results of the National Health and Nutrition Survey, which showed a continuous decrease in the smoking rate in young and older adult Japanese populations [ 15 ]. Therefore, we speculated that a continuous decrease in the smoking rate in our cohort could be one of the factors that contributed to the decreasing prevalence of VFs in this study.…”
Section: Discussionsupporting
confidence: 85%
“…They also reported that smoking increased the lifetime risk of VFs by 13% and 32% in women and men, respectively. This study demonstrated a significant decrease in the smoking rate of older adults in accordance with the results of the National Health and Nutrition Survey, which showed a continuous decrease in the smoking rate in young and older adult Japanese populations [ 15 ]. Therefore, we speculated that a continuous decrease in the smoking rate in our cohort could be one of the factors that contributed to the decreasing prevalence of VFs in this study.…”
Section: Discussionsupporting
confidence: 85%